Smile changes after intrusion of maxillary incisors with temporary anchorage devices (TADs) or accentuated compensating curve arch wire - Nahla Elsayed Gomaa; Neveen Mohamad Fakhry; Ghada Abdelfattah Elmehy; Mona A Montasser (Wolters Kluwer Medknow Publications, 2019)
Objective: The aim is to evaluate changes of smile and gingival line after intrusion of maxillary incisors using mini-implant anchorage system or conventional accentuated compensating curve archwire. Materials and Methods: Twenty participants having deep overbite with age ranged from 18 to 24 years were enrolled in this study and were divided into two groups of 10 each. Intrusion of maxillary incisors was performed using mini-implant anchorage system in group 1 and by conventional accentuated compensating curve archwire in group 2. For each participant, lip position, dental and skeletal measurements related to the gingival line were recorded from standardized photographs and cephalometric analyses. Statistical analyses including t-test and Chi-square were used to evaluate differences between groups. Results: There was an improvement of smile arc (consonance) from 30% smile consonance pretreatment to 90% consonance postintrusion in group 1, but the change was insignificant in Group 2. There was an increase in the outer intercommisural width in Group 2 compared to group 1 with a significant difference between both groups (P < 0.046). A significant decrease in the upper lip to upper incisal edge relationship in Group 1 and an insignificant decrease in Group 2 (P = 0.03 and P = 0.262, respectively) was detected. A significant decrease in overbite in Group 1and in Group 2 (P = 0.001) with an insignificant difference between both groups (P > 0.05) was also observed. Conclusion: Smile improvement in the mini-implant group was mainly the result of improved smile arc, increase in outer intercommisural width, decrease in upper lip to upper incisal edge relationship, and decrease in overbite. With the use of accentuated compensating archwires, the only significant change was increase in the interlabial gap.